Dose modifications in Asian cancer patients with hepatic dysfunction receiving weekly docetaxel: A prospective pharmacokinetic and safety study. Issue 2 (8th February 2016) - Syn, Nicholas Li‐Xun; Wang, Lingzhi; Wong, Andrea Li‐Ann; Soe, Mu‐Yar; Chuah, Benjamin; Chan, Daniel; Tan, Sing‐Huang; Soo, Ross Andrew; Lee, Soo‐Chin; Goh, Boon‐Cher; Yong, Wei‐Peng
Abstract : Hepatic dysfunction may modify the safety profile and pharmacokinetics of docetaxel in cancer patients, but no validated guideline exists to guide dose modification necessitated by this uncommon comorbidity. We carried out the first prospective study of a personalized dosage regimen for cancer patients with liver dysfunction treated with docetaxel. Weekly dosages were stratified by hepatic dysfunction classification as such: Category 1, normal; Category 2, mild – alkaline phosphatase, aspartate aminotransferase, and/or alanine aminotransferase ≤5× upper limit of normal (ULN), and total bilirubin within normal range; and Category 3, moderate – any alkaline phosphatase, and aspartate aminotransferase or alanine aminotransferase ≤5–10× ULN, and/or total bilirubin ≤1–1.5× ULN. Category 1, 2 and 3 patients received starting dosages of 40, 30, and 20 mg/m 2 docetaxel, respectively. Pharmacokinetics were evaluated on day 1 and 8 of the first treatment cycle, and entered into a multilevel model to delineate interindividual and interoccasion variability. Adverse event evaluation was carried out weekly for two treatment cycles. We found that docetaxel clearance was significantly different between patient categories ( P < 0.001). Median clearance was 22.8, 16.4, and 11.3 L/h/m 2 in Categories 1, 2, and 3, respectively, representing 28% and 50% reduced clearance in mild and moderate liver dysfunction patients, respectively. However, docetaxel exposure (area under the concentration–time curve) and docetaxel‐induced neutropenia (nadir and the maximum percentage decrease in neutrophil count) were not significantly different between categories. Median area under the concentration–time curve was 1.74, 1.83, and 1.77 mg·h/L in Categories 1, 2, and 3, respectively. The most common Grade 3/4 toxicity was neutropenia (30.0%). An unplanned comparison with the Child–Pugh and National Cancer Institute Organ Dysfunction Working Group grouping systems suggests that the proposed classification system appears to more effectively discriminate patients by docetaxel clearance and dose requirements. (ClinicalTrials.gov registration no. NCT00703378). Abstract : The authors report the first prospective study of a personalized dosage regimen for Asian cancer patients with liver dysfunction and treated with docetaxel. In this study, a clinically‐practicable hepatic dysfunction classification system for patients receiving docetaxel coupled to a dosing nomogram was developed and tested. This led to highly effective risk‐stratification and significant reduction of pharmacokinetic and pharmacodynamic variability.